Isolation and characterization of Bacillus cereus strain BUK_BCH_BTE1 for hexavalent molybdate reduction to molybdenum blue - Yusuf, Muhammad Rabiu; Harun, Fatima Abdullahi; Usman, Shehu; Jagaba, Ahmad Hussaini; Babandi, Abba; Muhammad, Amina Saíd; Yusuf, Fatima; Muhammad, Jahun Bashir; Auwal, Shehu Muhammad; Shukor, Mohd Yunus; Yakasai, Hafeez Muhammad (Elsevier, 2024)
Environmental contamination, primarily driven by human activities such as industrialization, urbanization, and agricultural practices, has led to the accumulation of heavy metals, particularly molybdenum, in urban soils. This contamination adversely affects plant growth, food security, and poses health risks. This study explores the bioreduction potential of Bacillus cereus strain BUKBCHBTE1 in transforming toxic hexavalent molybdate to molybdenum blue which is a less toxic state. The bacterium was isolated from agricultural soil in Nigeria and identified through 16S rRNA sequencing. Factors influencing molybdate reduction were optimized, including carbon and nitrogen sources, molybdate, and phosphate concentrations. Glucose was found to be the most effective carbon source, while ammonium sulfate was the preferred nitrogen source. Molybdate reduction was most efficient at a concentration of 20 mM, and a phosphate concentration of approximately 3.5 mM was optimal. These findings contribute to understanding molybdate bioreduction and its potential application in addressing heavy metal pollution in the environment. Bacillus cereus strain BUKBCHBTE1 shows promise as an effective agent for molybdate bioreduction, with implications for mitigating environmental and health hazards associated with molybdenum contamination.